Fungsi dan Pandangan Hidup Manusia dalam Babasan dan Paribasa Sunda Hidrologis - Kurniasih, Nia; Sudaryat, Yayat; Nurjanah, Nunuy (ppjbsip, 2025)
The purpose of this study is to examine the function and outlook of the Sundanese people as reflected in the Sundanese babasan and paribasa containing hydrological aspects. This study uses a qualitative descriptive method with content analysis to identify and interpret the meanings contained in the babasan and paribasa expressions. The results show that Sundanese babasan and paribasa related to water (hydrology) not only function as a means of communication, but also as a guide to morals, ethics, and a philosophy of life. Various proverbs such as